Oxymatrine for inflammatory bowel disease in preclinical studies: a systematic review and meta-analysis - Zhao, Xuan; Ye, Xiaolu; Gu, Yuting; Lou, Yijie; Zhou, Zhanyi; Ji, Yunxi; Xu, Daogun (Frontiers in Medicine, 2025)
BackgroundInflammatory Bowel Disease (IBD) is a chronic, idiopathic inflammatory disorder of the intestines. Oxymatrine (OMT) is a naturally active substance found in the desiccated roots of Sophora flavescens. It possesses anti-tumor, antiviral, and anti-inflammatory properties. In recent years, its therapeutic role in IBD has gradually been discovered. This review aims to explore the impact of OMT on inflammatory bowel disease by animal models.MethodsConduct a systematic search in the PubMed, Embase, Web of Science, Cochrane, and Medline databases. Using SYRCLE’s risk of bias tool to assess the bias risk and quality of the included studies. For some data presented as figures, Web Plot Digitizer 4.2 software was used to extract it. STATA 16.0 was selected for the final meta-analysis.ResultsAfter rigorous literature screening, 12 studies were included. The data analysis results indicated that the disease activity index (DAI), histopathological score (HS), interleukin-6 (IL-6), interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), nuclear factor-κB (NF-κB), and myeloperoxidase (MPO) activity in the IBD animal models significantly decreased following intervention with oxymatrine. Furthermore, OMT also extended the colon length in the animal models and improved the expression level of zonula occludens-1(ZO-1) and occludin. These results suggested that OMT may improve the condition of IBD through anti-inflammatory, antioxidative stress and protecting the intestinal barrier.ConclusionMeta-analysis suggests oxymatrine positively affects IBD animal models. This provides new insights for the clinical treatment of inflammatory bowel disease.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024570580, identifier [CRD42024570580].